2022
DOI: 10.1002/cam4.5031
|View full text |Cite
|
Sign up to set email alerts
|

Do breast cancer survivors with a recent history of clinical depression report worse experiences with care? A retrospective cohort study using SEER‐CAHPS data

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…As composite scores tend to cluster at the upper end of the rating scales, to use composite scores as main independent variables in our study, we categorized scores $90 as "excellent" and scores ,90 as "less than excellent," as previous work has done. [26][27][28] Receipt of GCT GCT for CRC was defined following NCCN stage-specific guidelines for the treatment of colon and rectal cancer. 29,30 We aimed to determine the receipt of standard patterns of treatment within general stage groupings (stage I, II, or III) for colon and rectal cancer, including care received from the time of surgical resection (as the most important component of curative treatment of CRC) to receipt of adjuvant therapy or cancer surveillance (dependent on general stage group).…”
Section: Cahps Patient Experiences With Carementioning
confidence: 99%
“…As composite scores tend to cluster at the upper end of the rating scales, to use composite scores as main independent variables in our study, we categorized scores $90 as "excellent" and scores ,90 as "less than excellent," as previous work has done. [26][27][28] Receipt of GCT GCT for CRC was defined following NCCN stage-specific guidelines for the treatment of colon and rectal cancer. 29,30 We aimed to determine the receipt of standard patterns of treatment within general stage groupings (stage I, II, or III) for colon and rectal cancer, including care received from the time of surgical resection (as the most important component of curative treatment of CRC) to receipt of adjuvant therapy or cancer surveillance (dependent on general stage group).…”
Section: Cahps Patient Experiences With Carementioning
confidence: 99%
“…Similarly, Arevalo et al . 3 , also utilizing the SEER database, identified that 7.6% of breast cancer patients were simultaneously diagnosed with depression. Therefore, Gao et al .’s study inevitably includes breast cancer patients with comorbid depression, given its reliance on the SEER database.…”
mentioning
confidence: 99%